2020
DOI: 10.2147/cmar.s253510
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circ_0046599 Promotes the Development of Hepatocellular Carcinoma by Regulating the miR-1258/RPN2 Network</p>

Abstract: Background Many studies have confirmed that circular RNAs (circRNAs) play a key role in the biological progression of cancers. However, the function of a novel circRNA, circ_0046599, in hepatocellular carcinoma (HCC) progression has not been explored. Methods Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to measure the expression of circ_0046599, microRNA (miR)-1258 and Ribophorin II (RPN2). Subcellular fractionation location assay was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…RPN2 may precisely interact with STAT3 and NF- κ B pathways. Circ_0046599 also promoted HCC development by influencing RPN2 [ 33 ]. Moreover, RPN2 can be detected in blood exosomes [ 45 ] and urinary exosomes [ 46 ], expanding its application in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…RPN2 may precisely interact with STAT3 and NF- κ B pathways. Circ_0046599 also promoted HCC development by influencing RPN2 [ 33 ]. Moreover, RPN2 can be detected in blood exosomes [ 45 ] and urinary exosomes [ 46 ], expanding its application in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that circRNAs play vital roles in the carcinogenesis through a competing endogenous RNA mechanism; e.g., circ_0046599 promoted HCC cell growth, glycolysis and motility by modulating miR-1258/RPN2 axis. 26 Circ_0000517 facilitated cell viability, colony formation, cell cycle processes, and repressed apoptosis in HCC cells by elevating TXNDC5 via decoying miR-1296-5p. 27 Nonetheless, the exploration of the functions of circ_0011232 pressed proliferation through targeting insulin-like growth factor type 1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…17 Circ_0046599 initiates HCC development and promotes metastasis via miR-1258/RPN2 signaling. 18 circ_0072995 was found to promote breast cancer For personal use only.…”
Section: Discussionmentioning
confidence: 99%